Derivation and differentiation of canine ovarian mesenchymal stem cells - Hill, Amanda B. T. [UNESP]; Hill, Jonathan E. B. T. [UNESP]; Bressan, Fabiana F.; Miglino, Maria Angélica; Garcia, Joaquim M. [UNESP] (MyJove, 2018)
Interest in mesenchymal stem cells (MSCs) has increased over the past decade due to their ease of isolation, expansion, and culture. Recently, studies have demonstrated the wide differentiation capacity that these cells possess. The ovary represents a promising candidate for cell-based therapies due to the fact that it is rich in MSCs and that it is frequently discarded after ovariectomy surgeries as biological waste. This article describes procedures for the isolation, expansion, and differentiation of MSCs derived from the canine ovary, without the necessity of cell-sorting techniques. This protocol represents an important tool for regenerative medicine because of the broad applicability of these highly differentiable cells in clinical trials and therapeutic uses.
Keywords: Developmental Biology; Differentiation; Dog; Homogeneous population; Isolation; Issue 142; Mesenchymal stem cell; Ovary; Plastic adherence; Stem cells